Effects of Long-Lasting High-Definition Transcranial Direct Current Stimulation in Chronic Disorders of Consciousness: A Pilot Study - Guo, Yongkun; Bai, Yang; Xia, Xiaoyu; Li, Jinju; Wang, Xiaoli; Dai, Yiwu; Dang, Yuanyuan; He, Jianghong; Liu, Chunying; Zhang, Hui (Frontiers in Neuroscience, 2019)
Transcranial direct current stimulation (tDCS) recently was shown to benefit rehabilitation of patients with disorders of consciousness (DOC). However, high-Definition tDCS (HD-tDCS) has not been applied in DOC. In this study, we tried to use HD-tDCS protocol (2 mA, 20 min, the precuneus, sustaining 14 days ) to rehabilitate 11 DOC patients. Electroencephalography (EEG) and Coma Recovery Scale–Revised (CRS-R) scores were recorded at before (T0), after a single session (T1), after 7 days’ (T2) and 14 days’ HD-tDCS (T3) to assess the modulation effects. EEG coherence was measured to evaluate functional connectivity during the experiment. It showed that 9 patients’ scores increased compared with the baseline. The central-parietal coherence significantly decreased at the delta band in DOC patients. EEG coherence might be useful for assessing the effect of HD-tDCS in DOC patients. Long-lasting HD-tDCS over the precuneus is promising for the treatment of DOC patients.